Great expectations: The promises and limits of innovation policy in addressing societal challenges - Laatsit, Mart; Grillitsch, Markus; Fünfschilling, Lea (Research policy, 2025)
In the policy discourse on societal challenges, it has become common to think of innovation policy as a key tool for addressing societal challenges. However, we argue that innovation policy has limits to what it can do, and for it to remain a useful tool for tackling societal challenges, it is necessary to re-assess its role. Thus, this paper addresses the following research questions: To what extent and how do innovation policy instruments meet the augmented expectations on innovation policy to address grand societal challenges? How can innovation policy instruments best be mobilised to contribute to a system transformation that tackles societal challenges? We analyse the potential of innovation policy instruments for addressing transformative failures and develop a new take on how innovation policy can deal with wicked problems by targeting cumulative transformations and critical intervention points. Acknowledging both the potential and limitations of innovation policy, we make a proposition for how an ambitious innovation policy contributing to solving societal challenges may be conceived. •It has become common to think of innovation policy as the universal tool for addressing societal challenges.•We argue that innovation policy has limits to what it can do and it is necessary to re-assess its role.•We analyse the adaptability of existing innovation policy tools for addressing transformative failures.•We differentiate between abrupt disruptive transformations and cumulative transformations.•We make a proposition for how an ambitious innovation policy contributing to solving societal challenges may be conceived.